(untitled) - DEVI KUMALA SARI, WIDIA (LATERNE, 2013)
Environmentalissuesbecome a global issuethatwe should finda solutiontosolve it. One component ofthe nationthathelped determinethe successful completion ofthe problemisschool, becauseschoolscan incorporateallcomponents ofeducation, includingenvironmentaleducation.Reading skills is a receptive activity, by reading the students will get information and understanding. But in practice, reading skills assessed more difficult than the other skills, the presentation of teaching materials in the school is also not effective, so the Teaching and Learning Activities (KBM) is not maximal. In order to achieve the learning objectives, teaching materials needed to make students independent learning, so learning is not only centered on the teacher (teacher centered). Therefore, arranged the German reading skills modules with adiwiyata insight for class XII semester one with the title "Lesenmit der Brille (brillant, leicht, und effektiv)".The formulation of the problem in this research is how the development of the module "Lesenmit der Brille" as supplementary German teaching materials SMA / MA?And the purpose of thisresearch to describe the development of the module "Lesenmit der Brille" as supplementary German teaching materials SMA / MA.This research uses development research with qualitative descriptive approach. Reference of development model that used is Thiagarajan development model, with research location in SMA Negeri 11 Surabaya. Thiagarajan development model consists of four stages of development, such as define, design, development, and disseminate. Because of time limitation and fund, this research is only until development stage. So, there is no distribution stage.Development of modules described in the following stages. (1) Validation the first module from validator, obtained to measure the feasibility assessment module with the percentage of 76.13% belonging to the feasible criteria. Development of modules described in the following stages. (1) Validation the first module from validator, obtained to measure the feasibility assessment module with the percentage of 76.13% belonging to the feasible criteria. (2) The results of the validation in the form of comments and suggestions, used as a reference to enhance the module into draft 2. (3) Furthermore, draft 2 module is tested on 28 students of class XII IPA 3 SMA Negeri 11 Surabaya, so it get responses from the students to measure the effectiveness of the module with the percentage of 95.95% which is considered with criteria very effective. The results of student responses data are used to enhance the draft 3 modules and as a material of writing the final report. Keywords: Development, Modules, Reading Skills